Differential Item Functioning on Physics items based on Computer Based Test in Junior High School Science Learning - Susongko, Purwo; Rosidin, Hanafie; Fatkhurrohman, M. Aji (IJIS Edu : Indonesian Journal of Integrated Science Education, 2021)
Learning in the era of the COVID-19 pandemic is carried out using media that can help, especially in theassessment section, learning can be done using a variety of assistive media such as the quizizz application.This study aims to determine the Differerential Item Functioning (DIF) contained in the physics questionsused for tests at SMP Al-Irsyad City of Tegal and SMP Muhammadiyah 1 Tegal City in class VIII of thematerial pressure on substances. This study uses an approach quantitative with primary data taken throughquizizz. The population of this research is the answer sheets of the eighth grade students of SMP in the cityof Tegal. The sampling technique used purposive sampling. The sample of students taken was 200respondents from SMP Muhamadiyah 1 in Tegal City and SMP Al-Irsyad in Tegal City. The analysistechnique uses the Rasch modeling with the Wald test. The results of the study concluded that the itemsdetected by DIF in the eighth grade science test set were substance pressure, namely items number 1 and17 and benefited male students, while items 11, 12 and 15 benefited female students.